2018
DOI: 10.3390/cancers10100375
|View full text |Cite
|
Sign up to set email alerts
|

Energy Stress-Mediated Cytotoxicity in Tuberous Sclerosis Complex 2-Deficient Cells with Nelfinavir and Mefloquine Treatment

Abstract: To find new anti-cancer drug therapies, we wanted to exploit homeostatic vulnerabilities within Tuberous Sclerosis Complex 2 (TSC2)-deficient cells with mechanistic target of rapamycin complex 1 (mTORC1) hyperactivity. We show that nelfinavir and mefloquine synergize to selectively evoke a cytotoxic response in TSC2-deficient cell lines with mTORC1 hyperactivity. We optimize the concentrations of nelfinavir and mefloquine to a clinically viable range that kill cells that lack TSC2, while wild-type cells tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Highly interestingly, many proteins were involved in energy metabolism (GO terms: ATP synthesis coupled electron transport, respirasome, NADH dehydrogenase complex). This is in line with previous studies that found the energy metabolism of Schistosomes, Streptococcus and mammalian cells to be affected by MEF ( Martín-Galiano et al, 2002 ; Manneck et al, 2012 ; Li et al, 2017 ; McCann et al, 2018 ). An important consideration is that binding to a drug does not necessarily lead to functional inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…Highly interestingly, many proteins were involved in energy metabolism (GO terms: ATP synthesis coupled electron transport, respirasome, NADH dehydrogenase complex). This is in line with previous studies that found the energy metabolism of Schistosomes, Streptococcus and mammalian cells to be affected by MEF ( Martín-Galiano et al, 2002 ; Manneck et al, 2012 ; Li et al, 2017 ; McCann et al, 2018 ). An important consideration is that binding to a drug does not necessarily lead to functional inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…Dual therapy by nelfinavir and bortezomib resulted in increased expression of CHOP and ATF4 in the tumors derived from xenograft models of mTOR hyperactive cells [ 70 ]. Moreover, combined therapy of nelfinavir and mefloquine (an analogue of chloroquine) or salinomycin (an anti-cancer antibiotic) resulted in activation of the ATF4-CHOP-GADD34 arm of the ER stress pathway in Tsc2 −/− mTOR-hyperactive cells [ 71 , 72 ]. Tian et al also reported phosphorylation of eIF2α and increased protein levels of ATF4 and CHOP in response to nelfinavir in glioblastoma cells [ 52 ].…”
Section: Potential Mechanisms Whereby Nelfinavir Exert Its Anti-camentioning
confidence: 99%
“…AMPK leads to inhibition of mTOR and activates autophagy at the downstream level, facilitating synergism between nelfinavir and autophagy inhibitors, such as chloroquine [ 69 ]. Activation of AMPK and downregulation of mTOR also occurred following dual treatment of nelfinavir and salinomycin or mefloquine [ 71 , 72 ]. The addition of energy substrate methyl pyruvate inhibited nelfinavir- and mefloquine-mediated AMPK activation and rescued from cell death [ 72 ].…”
Section: Potential Mechanisms Whereby Nelfinavir Exert Its Anti-camentioning
confidence: 99%
See 1 more Smart Citation
“…Anther research aimed to indirectly target rapamycin complex 1 (mTORC1) hyperactivity in cancers by exploiting homeostatic vulnerabilities within Tuberous Sclerosis Complex 2 (TSC2)-deficient cells [ 4 ]. Both chloroquine (an autophagy inhibitor) and nelfinavir (an ER stress inducer) selectively enhance cell death in mTORC1 hyperactive cells.…”
mentioning
confidence: 99%